Seroprevalence and risk factors of avian influenza H9 virus among poultry professionals in Rawalpindi, Pakistan. Issue 4 (July 2019) - Tahir, Muhammad F.; Abbas, Muhammad A.; Ghafoor, Tamkeen; Dil, Saima; Shahid, Muhammad A.; Bullo, Mir M.H.; Ain, Qurat ul; Ranjha, Muazam A.; Khan, Mumtaz A.; Naseem, Muhammad T.
Abstract: Background: Avian influenza H9 is endemic in commercial and backyard poultry in Pakistan and is a serious occupational health hazard to industry workers. This study aimed to determine the seroprevalence of avian influenza H9 infection in people working with poultry in Rawalpindi, Pakistan and assess the measures they took to protect themselves from infection. Methods: A cross-sectional study was conducted from December 2016 to May 2017 of 419 people working with poultry in Rawalpindi Division, including farm workers, vaccinators, field veterinarians, butchers and staff working in diagnostic laboratories. Potential participants were randomly approached and gave written consent to participate. Data were collected using a standardized questionnaire and serum samples were processed to detect H9 antibodies using the haemagglutination inhibition test. Results: Of the 419 participants, 406 (96.9%) were male. The mean age of the participants was 36.4 (SD 10.86) years. A total of 332 participants agreed to a blood test, 167 of whom were positive for A(H9) antibodies, giving an overall seroprevalence of 50.3%. Laboratory staff had the highest seroprevalence (100%) and veterinarians the lowest (38.5%). Vaccinators, butchers and farm workers had a seroprevalence of 83.3%, 52.4% and 45.5% respectively. Personals who used facemasks had significantly lower (P < 0.002) seroprevalence (29.6%) than those who never used them (90.6%). Similarly, those who always used gloves and washed their hands with soap had a seroprevalence of 32.8% compared with 89.0% in those who never took these precautions. Of the participants who handled antigens, 92.3% were seropositive. Conclusion: Laboratory staff and vaccinators are exposed to viral cultures and influenza vaccines respectively which may explain their high seroprevalence.